"The Forward Family" - Rorke Family (1904)
The Forward family (L-R): Hilda (Forward) Pike, Tryphena (Butt) Forward, Kathleen (Forward) Rorke, Edward Forward and Ernestine (Forward) Pike with John H. Penney (far right), during the winter. Ernest Edward Forward (1859-1944), son of Capt. Mark William Forward and Mary (Bemister) Forward, was born at Carbonear on 29 May 1859. He married Tryphena Butt (1858-1930) on 24 June 1885, and had three daughters: Ernestine (Forward) Pike (1887-1950), Hilda Samways (Forward) Pike (1889-1982) and Kathleen (Forward) Rorke (1894-1979). Ernest Forward died on 14 April 1944. The Rorke Family Photograph Collection contains 301 black and white and 28 colour photographs of the Rorke Family of Carbonear, Newfoundland, as well as the Forward and Bemister families from that area who are linked to it by marriage. Although spanning from the 1840s-1970s, most photos are from 1900-45, showing family events, homes and Newfoundland and Labrador locations. There is also an album of photos taken while James Rorke attended the Leys School in Cambridge, England.